Rotaviruses in infants with diarrhea studied by viral RNA electrophoresis in Ankara, Turkey - Ceyhan, Mehmet; Kanra, Güler; Yeniay, İhsan and Ciliv, Gönenç and Vesikari, Timo (The Turkish Journal of Pediatrics, 1987)
The viral RNA electrophoresis method was used to detect rotavirus in children under two years of age, admitted to two children’s hospitals in Ankara, Turkey, during the period from July 1984 through June 1985. Rotavirus was detected in 61 out of 375 children with diarrhea (16.3%), but in none of the 333 control children. Peak incidence of diarrhea occurred in December when the total incidence of diarrhea was the highest. The seasonal occurrence of rotavirus diarrhea in Turkey may have implications for planning of rotavirus vaccination. The viral RNA electrophoresis method has the advantages of simplicity, low cost, and specificity for studies of diarrhea in developing countries.